Association Between Hopelessness And Suicidal Ideation In Iranian Medical Students: A Cross-Sectional Study - Mohammad Hossein Sadeghian; Farnaz Etesam; Amin Nakhostin-Ansari; Samaneh Akbarpour; Mitra Akhlaghi (Health Psychology Research)
# Background and Objectives